(untitled) (Research, Society and Development, 2022)
Due to the increase in the number of cases of patients with chronic kidney disease, dentists tend to be more likely to see patients with this condition. Therefore, the objective of this work is the need for knowledge on the part of the professional about the conduct in relation to dental care given the specificities of the patient. A search was performed in Pubmed (MEDLINE) and BVS (Health Library) about the topic, selecting articles from 2000 to 2022. The following descriptors were used in English indexed in DeCS/MeSH (Descriptors in Health Science - decs.bvsalud.org): “Kidney Failure Chronic”, “Dentistry” and “Dental Care” associated with the Boolean operator “AND”, selected using the PICO strategy. The dentists must be taken some care to treat patients with chronic kidney disease, especially when performing invasive procedures, he must have a good communication with the nephrologist, caution when prescribing drugs and attention to biosafety standards. It is up to the dentists treat these patients rightly, in way that doesn’t worsen your health, given his high need for dental treatment and lack of programs that encourage these patients to visit the dentist frequently and care for his oral health.